Incretin-based therapies: a new potential treatment approach toovercome clinical inertia in type 2 diabetes - Nicolucci, A.; Rossi, M. C. (Acta Biomedica Atenei Parmensis, 2008)
Maintaining an adequate metabolic control is still a challenge in many patients with type 2 diabetes. Among the many factors advocated to explain the failure to achieve recommended goals, clinical inertia is increasingly recognised as a primary cause of poor glycaemic control. The existence of a “metabolic memory” strongly supports the adoption of a more aggressive treat-to-target approach, instead of waiting for treatment failure. This approach may be particularly important in the initial phases of the disease, to slow the progressive decline of beta-cell function and improve overall outcomes. The fear of hypoglycaemia and weight gain associated with most of the available treatments are among the main causes of clinical inertia, and strongly affect the attitudes of providers and patients toward therapy intensification. The incretin-based therapies represent a new potential goal-oriented treatment approach. Two classes of incretin-based drugs have been developed: GLP-1 mimetics (exenatide and liraglutide) and DPP-IV inhibitors (sitagliptin and vildagliptin). Incretino-mimetics have a peculiar mechanism of action that is associated with lack of hypoglycaemia and weight loss or neutrality; these characteristics may facilitate therapy intensification and help to attain established goals. Furthermore, they can induce benefits in terms of post-prandial hyperglicemia control and beta-cell function preservation. An early use of this class of drugs may show a positive impact on the disease progression and a delay in the need of insulin injections.